Implementation of a Novel Wilderness Medicine Simulation Course for Medical Students - Katherine A. Sprengel; Sophia Redpath; Kira L. Palazzo; Sara M. Hock (MedEdPORTAL)
Introduction Wilderness medicine is a growing field focused on delivering quality medical care in austere environments. Simulation-based education has proven effective in emergency and wilderness medicine, particularly in graduate medical education. We propose that introducing wilderness medicine concepts earlier in medical education as part of a high-fidelity simulation for medical students could both increase interest in wilderness medicine and have widely applicable educational benefits. Methods We developed a novel 1-day case-based simulation curriculum to be performed in a wilderness environment and invited undergraduate medical students to participate. A 25-question survey was administered before and after the simulation to assess subjective change across various topics. Results The 10 of 12 students who responded to the survey indicated that the simulation significantly increased their confidence in managing urgent medical cases and increased their interest in the wilderness medicine field. All students agreed that simulation was an effective way to learn this material. Discussion Implementing a wilderness medicine simulation in medical curricula appears feasible and provides a comprehensive model that can be easily adapted to other institutions.